Optimization of Wae Bobok based on community based tourism through green products and digitalization - Luh Komang Candra Dewi; Ni Nyoman Arini; I Ketut Andika Priastana (Universitas Muhammadiyah Magelang, 2024)
This activity aims to empower local communities in Wae Bobok Area through a community based tourism approach that integrates the concept of green products and digitalization. The method used in this activity is training and mentoring. The results of this activity show that the community based tourism approach by integrating the concept of green products and digitalization is able to empower local communities in the Wae Bobok Area significantly. Through mapping the potential of tourism and MSME products, it has succeeded in designing attractive tour packages by utilizing the uniqueness and beauty of nature and local culture. Assistance in packaging MSME products and green product innovation has encouraged the development of sustainable and environmentally friendly tourism products. Assistance in creating virtual tours have succeeded in increasing the exposure of Wae Bobok tourist destinations and MSMEs. By using digital technology, this destination can be reached by a wider community. Waste management assistance using the TPS3R system has succeeded in improving the cleanliness and comfort of tourist destinations. By continuing to develop this program and involving all stakeholders, it is hoped that Wae Bobok can continue to develop sustainably.